2017
DOI: 10.3174/ajnr.a5378
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Time Is Negatively Associated with Corpus Callosum Area in the Early Stages of CADASIL

Abstract: BACKGROUND AND PURPOSE:Reaction time was recently recognized as a marker of subtle cognitive and behavioral alterations in the early clinical stages of CADASIL, a monogenic cerebral small-vessel disease. In unselected patients with CADASIL, brain atrophy and lacunes are the main imaging correlates of disease severity, but MR imaging correlates of reaction time in mildly affected patients are unknown. We hypothesized that reaction time is independently associated with the corpus callosum area in the early clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In contrast, the two studies in CADASIL patients did not find lower brain volumes compared to controls. 29,30 To note, in this cohort, patients were younger (mean age 53) and were free of cognitive impairment.…”
Section: Part Ii: Quantification Of Brain Atrophy: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In contrast, the two studies in CADASIL patients did not find lower brain volumes compared to controls. 29,30 To note, in this cohort, patients were younger (mean age 53) and were free of cognitive impairment.…”
Section: Part Ii: Quantification Of Brain Atrophy: Resultsmentioning
confidence: 98%
“…Brain atrophy in SVD patients compared to controls (Table 2) We found only two studies in sporadic SVD 27,28 (from the same group) and two in CADASIL (based on the same small cohort) that compared brain volumes in patients with SVD to age-and sex-matched controls (Table 1). 29,30 Patients with sporadic SVD were included if they had a clinical lacunar stroke syndrome with a corresponding subcortical ischemic lesion on MRI as well as confluent WMH. 27,28 Both cross-sectional and longitudinal measures were reported in one study.…”
Section: Part Ii: Quantification Of Brain Atrophy: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Callosal atrophy has been observed in diseases with white matter lesions secondary to cerebral small vessel disease, such as vascular dementia and CADASIL (24). Future studies will tell whether the changes observed in our study will translate into cognitive impairment.…”
Section: Discussionmentioning
confidence: 60%